1960
DOI: 10.1152/ajplegacy.1960.198.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the cardiac pacemaker of the frog in relation to atrial fibrillation and to other atrial arrhythmias

Abstract: Observations of the activity of the sinus venosus of the frog heart indicate that function of the sinus is regular and sustained during suppression of the atria and ventricle by optimum amounts of acetylcholine. When atrial fibrillation was induced by acetylcholine injection and concurrent atrial distention, the sinus venosus also beat regularly and independently, neither affecting nor being affected by the adjacent fibrillating atria. In a number of observations, sinus impulses appeared to initiate momentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1967
1967
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(10- 5 to 10" 4 g/ml) dramatically inhibited aconitine-induced fibrillation in right atrial strips from rabbits. These findings were ascribed to the depressing effect of the drug on the pacemaker activity, and the authors concluded that acetylcholine has another effect on fibrillation besides the well-known one of facilitating fibrillation.…”
mentioning
confidence: 94%
“…(10- 5 to 10" 4 g/ml) dramatically inhibited aconitine-induced fibrillation in right atrial strips from rabbits. These findings were ascribed to the depressing effect of the drug on the pacemaker activity, and the authors concluded that acetylcholine has another effect on fibrillation besides the well-known one of facilitating fibrillation.…”
mentioning
confidence: 94%
“…Nelson and Smith (27) observed sinus venosus impulses in the frog heart during acetylcholine perfusion, which apparently initiated momentary fibrillation in adjacent atrial areas and led eventually to a sustained and generalized arrhythmia. In the dog, Scherf et al (18) demonstrated that acetylcholine-induced atrial fibrillation could be stopped by simultaneously cooling the sinus and A-V node regions and that the arrhythmia recurred upon rewarming.…”
Section: Discussionmentioning
confidence: 99%